Intramedullary Cysticercosis- An Uncommon Entity Even in the Presence of Intracranial Neurocysticercosis - Walia, Gurpreet Kaur; Baveja, Puneet; Verma, Shipra; Kumar, Sanjay; Jain, Atul; Dudhal, Rahul (Annals of Pathology and Laboratory Medicine, 2020)
Neurocysticercosis (NCC) is described as the central nervous system involvement by a parasitic infection caused by a nematode, Taenia solium. By far, NCC is the most common parasitic infection of central nervous system in the world. In the developing countries like India, NCC is a leading cause of epilepsy in all age groups. Here, we present a case of a 36-year-old male who was a known case of multiple NCC involving the brain having cognitive dysfunction and presented with difficulty in walking and sudden onset weakness of right lower limb. On contrast enhanced MRI of spine, an intramedullary lesion was seen at D7- D8 level, which was confirmed on histopathological examination of the excised tissue as NCC. During clinical follow-up, the patient has shown significant neurological improvement.